New approach towards imaging lambda-DNA using scanning tunneling microscopy/spectroscopy (STM/STS) - Dey, Shirshendu; Pethkar, Sushama; Adyanthaya, Suguna D.; Sastry, Murali; Dharmadhikari, C. V. (Bulletin of Materials Science, 2008)
A new methodology to anchor A-DNA to silanized n-Si(111) surface using Langmuir Blodget trough was developed. The n-Si (111) was silanized by treating it with low molecular weight octyltrichlorosilane in toluene. Scanning tunneling microscopy (STM) image of lambda-DNA on octyltrichlorosilane deposited Si substrate shows areas exhibiting arrayed structures of 700 nm length and 40 nm spacing. Scanning tunneling spectroscopy (STS) at different stages depict a broad distribution of defect states in the bandgap region of n-Si(111) which presumably facilitates tunneling through otherwise insulating DNA layer.
National Review and Coordination Meeting on Nanoscience and Nanotechnology, Hyderabad, INDIA, 2007
Keywords: DNA; Langmuir Blodget technique; Scanning tunneling microscopy; silanization